Have adults lost their sense of play? An observational study of the social dynamics of physical (in)activity in German and Hawaiian leisure settings - Ansgar Thiel; Hendrik K. Thedinga; Samantha L. Thomas; Harald Barkhoff; Katrin E. Giel; Olesia Schweizer; Syra Thiel; Stephan Zipfel (BMC, 2016)
Abstract Background Physical inactivity is one of the biggest health problems nowadays. Recent research shows that socio-cultural barriers to physical activity are mostly related to modern lifestyles. However, there is a lack of research on how social and group dynamics influence engagement in physical activity. Furthermore, there are few cross-cultural studies that have compared the social dynamics of (in)activity in different cultural settings. This paper therefore aims to analyse how social group dynamics influence physical activity and inactivity in informal social environments and whether physical activity is influenced by the socio-cultural settings. Methods The paper presents the qualitative data collected within a covert participant observation study. Data was collected by keeping observational notes in order to record typical, regular patterns regarding physical (in)activity related behaviour of groups at an artificial open air swimming pool in Germany and a natural pond in Hawai'i. The data collection period was eight and a half months. Data was interpreted based on constant comparative analysis in order to identify most generative patterns in the field notes. Results Group structures appear to play a significant role regarding the activity of the group members. In this study, we identified four key factors that influence group based physical activity: 1) Physical activity seems to be a group disturbing behaviour particularly in larger groups of adults; 2) Physical activity appears to be more functional and less joyful in adults than in children; 3) Group activity is influenced by (in)activity anchors, including 'domestication' of a group's site, obesity, and controlling parents. 4) Physical activity is to a certain extent socially contagious, particularly with regard to playful activities. Conclusions Successful promotion of physical activity should target the social structures of inactive individuals' groups. In this regard, one of the main problems is that fun and wellbeing, as very important targets of public health strategies for the adult population, appear not to be compatible with physical activity. Developing strategies to reframe physical activity rather as 'fun' and less as functional may be one way to engage inactive individuals in physical activity in leisure settings.